Guidelines for driving vocational workforce into target industries for economic development in Thailand - Pearnpitak, Kittipong; Sirisunhirun, Somboon (Kasetsart Journal of Social Sciences, 2023)
The objective of this study was to suggest guidelines for driving vocational workforce into target industries for economic development in Thailand. Data were collected from interviews with executives of vocational institutions and related government agencies to create a diagram. The study found that the labor force in the EEC area was insufficient to meet the needs of the target industries. It must consider from the readiness of family institutions, educational institutions, enterprises, and related agencies to determine the direction of joint operations. However, consideration must be given to the dynamics of technology that affect the formulation of courses, training, and the creation of new jobs to accommodate foreign advanced technologies. Therefore, preparation is required in all dimensions. In particular, the vocational workforce plays an important role in the target industries in enhancing competitiveness for the country’s sustainable economic development.